On extension of the limit theorem of renewal theory and its application - Bondarenko, A. (Інститут математики НАН України, 2006)
An extension of the limit theorem of renewal theory on the case of semi-Markov process with an atom of the stationary distribution of the embedded Markov chain is obtained in this paper. The obtained result is used for ﬁnding an analytic solution of a reliability problem for a system with protection.